2010
DOI: 10.1097/qad.0b013e32833e6cfb
|View full text |Cite
|
Sign up to set email alerts
|

Population-based V3 genotypic tropism assay: a retrospective analysis using screening samples from the A4001029 and MOTIVATE studies

Abstract: Despite differences in sensitivity for predicting non-R5 HIV, week 8 and 24 week virological responses were similar in this treatment-experienced population. These findings suggest the potential utility of V3 genotyping as an accessible assay to select patients who may benefit from maraviroc treatment. Optimization of the predictive tropism algorithm may lead to further improvement in the clinical utility of HIV genotypic tropism assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 17 publications
2
105
1
Order By: Relevance
“…GTT provides a rapid, inexpensive and widely available approach for tropism testing. Clinical outcome studies have recently indicated that GTT is reliable for predicting virological responses to maraviroc in both treatment-experienced and treatment-naïve patients [17,18]. In these studies, GTT was applied to plasma samples of patients with a viral load of 41000 copies/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GTT provides a rapid, inexpensive and widely available approach for tropism testing. Clinical outcome studies have recently indicated that GTT is reliable for predicting virological responses to maraviroc in both treatment-experienced and treatment-naïve patients [17,18]. In these studies, GTT was applied to plasma samples of patients with a viral load of 41000 copies/mL.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the FPR cut-off, the greater the likelihood of detecting CXCR4-using virus, but also of falsely identifying a sequence as X4. Clinical evidence provides support for the validity of using an FPR cut-off of approximately 5-10% [17,18].In a comparison of the results for 165 simultaneous plasma RNA/proviral DNA samples, the concordance in predicted tropism between the two sample types was high, ranging from 95.2% at an FPR of 10% to 96.4% at an FPR of 5%. In addition, the concordance in absolute FPR values for the two sample types was very good (r 5 0.8510).…”
mentioning
confidence: 99%
“…[22][23][24][25] In addition, in previous studies genotypic tropism tests were retrospectively validated, while here we show that selection of prospective maraviroc regimens using genotypic or phenotypic assays is associated with similar virological and immunological responses. In contrast with expectations, non-R5 tropism was not negatively associated with virological response.…”
Section: Rossetti Et Almentioning
confidence: 94%
“…These tests detect substitutions at the V3 region of gp120 HIV-1 gene in order to predict the CXCR4 use by viruses present in the patient's quaispecie. Although phenotypic and genotypic tests do not fully agree with each other, genotypic tests are probably equally able to predict virologic treatment failure in maraviroc containing antiretroviral schemes [47] and have been advocate as preferential in some guidelines. [49] 3.…”
Section: E Hiv-1 Tropismmentioning
confidence: 99%
“…[47] Therefore, a tropism test before treatment with these drugs is required; gold standard tropism tests being the phenotypic based tests. One phenotypic tropism test constructs pseudoviruses containing the gp160 of patient's viruses and a backbone of HIV-1 laboratory virus plus the luciferase gene.…”
Section: E Hiv-1 Tropismmentioning
confidence: 99%